Analisis Proses Rekrutmen dan Seleksi Calon Karyawan dalam meningkatkan Kinerja Karyawan Pada Hotel Zahra Syariah Kendari - susanti, marni; Abdullah, Akhyar; nurjannah, nurjannah (Universitas Halu Oleo, 2019)
The purpose of this study was to determine and describe the Analysis of the Process of Recruitment and Selection of Prospective Employees in improving Employee Performance at the Zahra Syariah Hotel in KendariInformants in this study were the General Manager of the Zahra Syariah Hotel in Kendari, the HRD Manager, the Head of Marketing and the Head of Accounting from the Zahra Syariah Hotel in Kendari. Then the information obtained was analyzed qualitatively.The results of this study indicate that the analysis of the recruitment and selection process of prospective employees in improving employee performance at the Zahra Syariah Hotel in Kendari, accepting prospective employees from the SMK vocational school and Kendari Vocational Training Center (BLK) that must meet established requirements such as ID card, domicile card, appearance interesting, must have a able-bodied letter from a doctor and others, and the method of recruiting prospective employees is still using a closed test, while the selection of employees must meet predetermined criteria with regard to educational qualifications, work experience, physical condition and personality of employees, and before employees work the Hotel Zahra Syariah provides training and practice in advance so that employees can have knowledge so as to open opportunities to advance and work well. The workforce at the Zahra Hotel Syariah has been very good in terms of work skills, quality of work, responsibility responsibility, discipline and cooperation. Zahra Syariah Hotel also rewards employees who work well, giving awards once a year with the aim to improve and motivate employees to always work responsibly, with high discipline, and be able to work with one another